Copper‐Catalyzed Alkylation of Thiophenols with Benzyltrimethylammonium Triflates. Issue 1 (30th November 2017) - Lu, Fangling; Chen, Ziyue; Li, Zhen; Wang, Xiaoyan; Peng, Xinyue; Li, Cong; Li, Ru; Pei, Hongqiao; Wang, Huamin; Gao, Meng
Abstract: A copper‐catalyzed cross coupling of thiophenols with benzyltrimethylammonium triflates has been developed. Various kinds of aryl and heteroaryl thiophenols and alkylthiols demonstrated to be efficient substrates, generating the desired alkyl thioethers in moderate to good yields. Meanwhile, different benzyltrimethylammonium triflates could be well tolerated. Abstract : C−S bond formation : A copper‐catalyzed cross‐coupling of thiophenols with benzyltrimethylammonium triflates has been developed. Various kinds of aryl and heteroaryl thiophenols and alkylthiols demonstrated to be efficient substrates, generating the desired alkyl thioethers in moderate to good yields.